The intersection between tourism and sharing economy from a different angle: the Home4creativity case study - Fortezza, Fulvio; Berdicchia, Domenico; Masino, Giovanni (Piccola Impresa / Small Business, 2019)
In the last few years the so-called sharing economy has been the subject of a great deal of attention, in tourism as well, with particular regard to: - the effects of the Airbnb model on the tourism industry and related drivers; - the transformative power of collaborative tourism experiences, especially Couchsurfing. We aim to enhance this body of knowledge by taking into consideration the combined effect of a hybrid set of collaborative practices (i.e., renting, bartering, and sharing) that goes along a continuum between market exchange and shared sociality. We purport to do that through a special project from Italy, i.e., a digital platform that aims to connect people who want to share their homes, working spaces, time, and skills with others and who strive to change their lives. The guests can either pay a fee for the various services or give their time, artistic skills or entrepreneurial ability in return. This case study portrays a new value creation model in tourism.